Water Injection and Dust Reduction Technology for Thick Coal Seam in 5011 Fully Mechanized Caving Face of Ma Di Liang Coal Mine - Kan, Lei; Wang, Guodong (International Journal of Natural Resources and Environmental Studies, 2025)
During the mining process of the 5011 comprehensive mining face of Ma Di Liang Coal Mine, the coal body is crushed, resulting in a large amount of dust being generated when the comprehensive mining machine cuts the coal body. Through the study of the temporal and spatial evolution laws of dust dispersion during coal mining operations, the sources of coal dust are analyzed, the influencing factors of the water injection effect in the coal seam are studied, the mechanism of dust reduction by water injection in the coal seam is revealed, and the water injection process for the 5011 comprehensive mining face is formulated. Finally, the dynamic and static collaborative water injection method is adopted to effectively ensure the uniformity and progress of water injection on the working face, thereby achieving significant dust reduction effects. The research results have significant implications for the dust control and safe production of Ma Di Liang Coal Mine.